2005
DOI: 10.1016/j.envint.2005.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of organochlorine pesticides (HCH and DDT) in sediments collected from East China Sea

Abstract: Sediments used in this study were collected from different depths of eight sites in East China Sea in November 2002. The levels and distribution patterns of the selected organochlorine pesticides (OCPs = p,pV-DDT, o,pV-DDT, p,pV-DDE, p,pV-DDD, a-, h-, g-and y-HCH) in samples were investigated by the technique of sonication extraction followed by the analysis of gas chromatography (GC) coupled with a micro-electron capture detector (AECD). The concentrations of AHCH and ADDT in the surface sediments were in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(73 citation statements)
references
References 21 publications
(24 reference statements)
10
61
1
1
Order By: Relevance
“…HCH isomers have been identified as a worldwide contaminant (Doong et al 2002). The properties of higher water solubility, vapor pressure, and biodegradability, and lower lipophilicity and particle affinity, of HCH relative to DDT (Yang et al 2005a) could account for the higher concentrations of HCH in sediments. These results were inconsistent with previous observations on OCP residues in freshwater sediments in China due to the difference in physicochemical and biochemical characteristics (Tang et al 2007).…”
Section: Concentrations Of Hch and Ddt In Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCH isomers have been identified as a worldwide contaminant (Doong et al 2002). The properties of higher water solubility, vapor pressure, and biodegradability, and lower lipophilicity and particle affinity, of HCH relative to DDT (Yang et al 2005a) could account for the higher concentrations of HCH in sediments. These results were inconsistent with previous observations on OCP residues in freshwater sediments in China due to the difference in physicochemical and biochemical characteristics (Tang et al 2007).…”
Section: Concentrations Of Hch and Ddt In Sedimentsmentioning
confidence: 99%
“…b-HCH is the least water-soluble isomer of HCH, has a higher vapor pressure and octanol/water partitioning coefficient, and is relatively resistant to microbial degradation, which makes it the most stable isomer (Willett et al 1998;Yang et al 2005b). After a long period of weathering, a-and c-HCH can be transformed into b-HCH (Yang et al 2005a). The observation of a greater relative proportion of b-HCH (8% of P HCH) than a-and c-HCH indicated that the HCH was mainly due to historical use (Toan et al 2007) and that technical HCH has not recently been used in this region.…”
Section: Relative Proportions Of Hch and Ddt Components And Possible mentioning
confidence: 99%
“…Soil contamination with organochlorine pesticides (OCPs) such as dichlorodiphenyltrichloroethane (DDT), hexachlorocyclohexane (HCH), chlordane, and heptachlor is of great concern due to their toxicity, bioaccumulation, and persistence in the environment (Yang et al 2005). the wide distribution of their residues and their carcinogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…HCHs are usually used as two formulations. One is technical HCH that is a mixture of 55-80 % a-, 5-14 % b-, 8-15 % c-, and 2-16 % d-isomers (Yang et al 2005). The other is lindane, which contains approximately 99 % of c-HCH (the HCH isomer of highest pesticide activity).…”
Section: Potential Sources Of Pahs and Ocpsmentioning
confidence: 99%